Four-step simulation toolchain to assess the effectivity of noise reduction measures for shrouded tail-rotors - Stadlmair, N.; Redmann, D.; Hirsch, F.; Zappek, V. (My University, 2021)
This paper presents a simulation tool-chain to study the effect of design changes on shrouded rotorcraft (tail-)rotors on its noise signature. Basically, the approach consists of four steps: The first step involves the simulation of the flow-field of the shrouded tail-rotor. The second step involves the computation of the noise far-field using the Ffowcs Williams-Hawkings (FW-H) equations in its Farassat 1A formulation. Both, step 1 and 2 are performed in the time domain. Afterwards, results are transformed to the frequency domain which improves computational efficiency and flexibility significantly. The third step is the computation of the acoustic transfer matrix to include the near-field effects of the structural elements of the tail-rotor. For this purpose, a high-fidelity finite-element model of the fluid domain surrounding the shrouded tail-rotor is introduced which is based on the frequency space formulation of the Helmholtz equations. The fourth and last step in the simulation tool chain is a terrain noise model which is based on acoustic ray tracing while results from the computed sound pressure level spheres serve as a source of ray release. The terrain noise simulation is capable to consider atmospheric attenuation as well as varying environmental and geographical conditions. In the present study, the prediction of the frequencies and relative sound pressure levels was demonstrated with acoustic measurement data acquired at a full-scale single component test-rig. The proposed toolchain uses the Kopter AW09’s tail-rotor as an illustrative example to study the acoustic signature for hover and two forward-flight conditions. In this context, the spatial distribution of the noise emissions as well as the noise footprint on the ground are discussed. This serves to highlight the impact of shroud near field effects. As a practical example, the effect of a generic liner implemented upon the inner surface of the shroud is discussed. For this, directivity and noise footprint on the ground are used to benchmark the effectiveness of the liner in terms of global and local noise level reduction.